Characterisation of hydroxyapatite-coated titanium for biomedical applications - Lee, Jiin Woei (2014)
Orthopaedic implants function to replace or support damaged or diseased bone. Due to a global rise in demand, there is a need to prolong the service life of these implants. The current work focuses on crystallised hydroxyapatite (HA)-coated titanium (Ti) implants. One specific problem during the annealing of as-deposited amorphous HA, to induce crystallisation, is the formation of unwanted titanium oxide (Ti-O) species at the HA/Ti interface that leads to HA layer disruption. This necessitates the introduction of a diffusion barrier layer at the HA/Ti interface. Another reason for implant failure is bone disintegration around the implant; therefore enhancing early bone cell growth on the implant may be beneficial.